A Simplification and an Extension of the Bernhard-deFARO Sufficient Condition for a Unique Non-Negative Internal Rate of Return - Bernhard, Richard H. (Journal of Financial and Quantitative Analysis, 1980)
Richard H. Bernhard, A Simplification and an Extension of the Bernhard-deFARO Sufficient Condition for a Unique Non-Negative Internal Rate of Return, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 1 (Mar., 1980), pp. 201-209